Role of EDTA and cysteine hydrocloride as additivies in EYC and TEFC . extenders for preservations of beetal bulk's spermatozoa - SINGH, K H MANI; SINGH, M P; SINHA, A K; SINGH, D K (The Indian Journal of Animal Reproduction, 2023)
The semen sample ofBeetal bucks extended in six extenders ( EYC, EYC + EDTA, EYC + Cysteine Hcl,TEYFC. TEYFC + EDTA and TEYFC + Cysteine Hcl) and preserved at refrigerator temperature were evaluated formotility, livability and abnonnality up to 96 hours at 24 hours interval.The effects of extender and additive onseminal attributes were significant ( P ~ 0.0 I). The post preservation seminal attributes were better in TEYFCextender incorporated with Cysteine Hcl as compared to other extenders , indicating that TEYFC is an ideal semendiluent as compared to EYC and that inclusion ofO.0 I% Cysteine Hcl in both extenders showed beneficial effecttowards improving the keeping quality of liquid semen of Beetal bucks.
Keywords: EDTA; cysteine Hcl; buck; spermatozoa